2000
DOI: 10.1034/j.1399-3003.2000.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 is a potent inhibitor of secretory leukoprotease inhibitor expression in a bronchial epithelial cell line

Abstract: Obliterative bronchiolitis (OB) is the major long-term complication following lung and heart-lung transplantation. In bronchoalveolar lavage fluid samples obtained from patients suffering from OB, a marked increase in the number of neutrophils and elevated expression of transforming growth factor (TGF)-b 1 had been found. The goal of the study was to evaluate whether TGF-b 1 is capable of interfering with the expression of the secretory leukoprotease inhibitor (SLPI), the dominating defence of the conducting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
(29 reference statements)
3
25
0
2
Order By: Relevance
“…For LOX, this is a likely possibility because it is a known transcriptional target of TGF-␤1 (65). The intermediate steps leading to the inhibition of TGF-␤1 and IGFBP-3 gene expression upon increased expression of SLPI cannot be deduced from the present studies, although a regulatory loop arising from TGF-␤1 inhibition of SLPI gene expression, as demonstrated here, is consistent with reports observed for a bronchial epithelial cell line (66). In further agreement with the present results, a negative correlation between SLPI and TGF-␤1 was reported in SLPI null mutant mice (25).…”
Section: Fig 8 Effects Of Tgf-␤1 On Ishikawa Cell Gene Expressionsupporting
confidence: 91%
“…For LOX, this is a likely possibility because it is a known transcriptional target of TGF-␤1 (65). The intermediate steps leading to the inhibition of TGF-␤1 and IGFBP-3 gene expression upon increased expression of SLPI cannot be deduced from the present studies, although a regulatory loop arising from TGF-␤1 inhibition of SLPI gene expression, as demonstrated here, is consistent with reports observed for a bronchial epithelial cell line (66). In further agreement with the present results, a negative correlation between SLPI and TGF-␤1 was reported in SLPI null mutant mice (25).…”
Section: Fig 8 Effects Of Tgf-␤1 On Ishikawa Cell Gene Expressionsupporting
confidence: 91%
“…Oral and genital mucosae differ in several aspects that may alter their susceptibility to this virus, including the architecture of the epithelium, composition and viscosity of the fluids bathing the sites, and local immune responses. In addition, tissue-specific differences in SLPI regulation by HIV-1 may contribute to tissue susceptibility, as treatment with tumor growth factor ␤1 suppressed SLPI mRNA levels in respiratory epithelial cells (21) but had the opposite effect in endometrial epithelial cells (50). Characterization of the SLPI response to HIV-1 in nonoral mucosal tissues will shed light on this important issue.…”
Section: Discussionmentioning
confidence: 99%
“…strated in cultured keratinocytes (Tanaka et al, 2000); or in turn, SLPI might suppress inflammatory cytokine gene expression as shown after hepatic ischemic reperfusion injury (Lentsch et al, 1999) or affect cytokine activity (such as TGF-␤) as shown in cutaneous wound healing in SLPI-null mice (Ashcroft et al, 2000). In addition, the expression of SLPI preceded that of TGF-␤1 after ischemic brain injury (Wang et al, 1995), and TGF-␤1 was shown to inhibit SLPI expression in cultured bronchial epithelial cells (Jaumann et al, 2000). The temporal expression profile of SLPI with inflammatory mediators and leukocyte accumulation in the brain after ischemic injury again suggests that SLPI may be associated with regulation of inflammatory response.…”
Section: Slpi Expression Protects Brain From Ischemic Injury 837mentioning
confidence: 99%